ANALISIS KELAYAKAN BISNIS DITINJAU DARI ASPEK PEMASARAN DAN KEUANGAN PADA WARKOP LUXFERRELOUNGE - Ali Safran Pasaribu; M Ziqhri Anhar Nasution (Kampus Akademik Publiser, 2026)
This study aims to qualitatively analyze the business viability of Warkop Luxferrelounge, specifically focusing on its operational financial management framework and marketing strategy implementation to mitigate the risk of structural failure. A descriptive qualitative approach utilizing a single case study method was employed. Data were collected through in-depth interviews and passive participant observation involving the owner, employees, and customers; validity was verified via triangulation, and analysis was conducted using the Miles and Huberman interactive model. The results indicate that the business is viable from a marketing perspective, achieved by implementing an inclusive hybrid concept and relying on organic marketing strategies driven by Electronic Word-of-Mouth (e-WOM) rather than incurring heavy paid promotion costs. Financially, the business demonstrates positive viability and resilience through disciplined governance, including the strict separation of business and personal accounts, Standard Operating Procedures (SOPs) for daily cash reconciliation, and projections for daily raw material procurement to prevent waste. In conclusion, Warkop Luxferrelounge is a highly viable MSME entity that exhibits strong resilience amidst market saturation. The study demonstrates that the sustainability of culinary MSMEs in the modern era does not necessarily depend on massive promotional budgets but rather hinges on accurately targeting market niches, maintaining cash flow transparency, and upholding managerial discipline.